Pengembangan Media Pembelajaran Interaktif Berbasis Pendidikan Karakter Pada Pembelajaran Matematika SMP Kelas VII Menggunakan Powerpoint - Anisah Anisah; Dita Yuzianah; Mujiyem Sapti (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Anisah. 182140060. "Development of Character Education-Based Interactive Learning Media in Class VII Middle School Mathematics Learning Using Powerpoint". Thesis. Mathematics education. FKIP. Purworejo Muhammadiyah University. 2023. The aim of this research is to develop and determine the feasibility of the learning media that has been developed. The media product in this study is in the form of interactive learning media based on character education using Powerpoint in learning mathematics for seventh grade junior high school on integer material. This research uses the type of development research (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques in this research were carried out by means of interviews, questionnaires and tests. The instruments used include media expert and material expert validation sheets, teacher response questionnaire sheets and student responses, and final test questions. The subjects in this research were class VIID students at SMP Negeri 18 Purworejo. Data analysis in this study was the validity data analysis of media experts and material experts, analysis of teacher response data and student responses, and analysis of final test completeness data. The results of the media expert's assessment obtained a total score of 66 with valid criteria and material experts obtained a total score of 29 with the validity calculation formula obtaining results with valid criteria, from the teacher response questionnaire and student responses obtained an average total score of 85.1 with practical criteria, from The results of the final question test obtained a completion percentage of 84% with effective criteria. Based on the research results, this mathematics learning media was declared valid, practical and effective. Thus it can be concluded that interactive learning media based on character education in class VII SMP mathematics learning using PowerPoint is appropriate to use as a learning medium.